2,4-diaryl-substituted quinoline corrosion inhibitor and preparation method and application thereof
Patent Information
- Application Number
- CN202611304974.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-09
AI Technical Summary
该技术中母核为异喹啉并硫酮-酮基杂环,与2,4-二芳基喹啉结构完全不同;依赖原位聚合成膜,成膜条件苛刻、重复性差、适用范围受限;必须复配有机锑类增效剂,毒性较高、环境友好性差;无定向电子调控、疏水致密化、π-π 堆积强化设计,分子结构不可调、性能可控性弱
本发明提供了一种2,4-二芳基取代喹啉缓蚀剂,该缓蚀剂包含2,4-二芳基喹啉母核,该母核通过2位电子调控、4位疏水调控、芳环π-π堆积、N 原子季铵化,可制得单子或双子季铵盐。母核由苯胺、苯甲醛、苯乙烯在对甲苯磺酸催化下无溶剂合成,其具有丰富的平台改性潜力,具有在高温高压酸化缓蚀方面的应用前景。
Smart Images

Figure CN122878261A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of corrosion inhibitor technology, specifically relating to a 2,4-diaryl-substituted quinoline corrosion inhibitor, its preparation method, and its application. Background Technology
[0002] As oil and gas resource development continues to extend into deeper, ultra-deep, and unconventional reservoirs, metal equipment is exposed to high-temperature, high-pressure, and strongly acidic fluid environments for extended periods during operations such as acidizing, fracturing, acid fracturing, and production, leading to increasingly prominent corrosion problems. To mitigate the corrosion of tubing, casing, and surface equipment by acidic media, corrosion inhibitors are typically added to the operating fluids to form a protective film, thereby reducing the metal corrosion rate.
[0003] Currently, the mainstream corrosion inhibitors used in industrial oil and gas fields include organic corrosion inhibitors such as imidazoline, quaternary ammonium salts, pyridine / quinoline, amides, and Schiff bases. Their mechanism of action relies on the adsorption of nitrogen-, sulfur-, or oxygen-containing functional groups on metal surfaces. However, they generally suffer from insufficient temperature resistance, poor adsorption film stability, and fixed modification methods, making it difficult to meet the requirements of deep wells and long-term operations.
[0004] There are many types of corrosion inhibitors available for oil and gas fields, mainly including the following categories: Imidazoline corrosion inhibitors: These are among the most widely used types of corrosion inhibitors, possessing excellent adsorption properties and corrosion inhibition effects. However, imidazoline corrosion inhibitors are prone to hydrolysis at high temperatures, leading to a significant decrease in their corrosion inhibition performance; their temperature resistance generally does not exceed 120℃.
[0005] Quaternary ammonium salt corrosion inhibitors: They have excellent water solubility and broad-spectrum bactericidal properties, but their corrosion inhibition mechanism mainly relies on electrostatic adsorption. Their adsorption stability is poor in strong acid environments, and long-term use can easily lead to drug resistance problems.
[0006] Pyridine or quinoline corrosion inhibitors: These inhibitors utilize the π electrons of nitrogen-containing heterocycles to form coordinate bonds with the metal surface, resulting in strong adsorption. However, existing quinoline corrosion inhibitors have relatively simple molecular structures and limited modification sites, making it difficult to meet the comprehensive performance requirements under complex operating conditions.
[0007] Amides and Schiff bases are corrosion inhibitors that form stable adsorption on metal surfaces through C=N double bonds and carbonyl groups in their molecules. However, their synthesis routes are complex and costly, and they are prone to decomposition in high-temperature acidic environments.
[0008] The above-mentioned corrosion inhibitors generally share the following common problems: First, their temperature resistance is insufficient. Most corrosion inhibitors experience a significant decrease in inhibition efficiency when temperatures exceed 80°C. This is mainly because high temperatures accelerate the desorption of inhibitor molecules from the metal surface and also promote their thermal degradation. For deep well acidizing operations, bottom-hole temperatures often exceed 100°C, even reaching over 150°C, making it difficult for existing corrosion inhibitors to meet the requirements.
[0009] Secondly, the adsorption film has poor stability. The adsorption film formed by the corrosion inhibitor on the metal surface is easily washed away and destroyed in flowing acidic media, especially under high flow rate conditions. The integrity of the protective film is difficult to maintain, resulting in a sharp decrease in the corrosion inhibition effect.
[0010] Secondly, the modification methods are fixed. Existing corrosion inhibitor molecules have a limited number of modifiable sites, making it difficult to precisely control them for different operating conditions. For example, in high-salt environments, it is necessary to enhance the hydrophobicity of the molecules, and to address compatibility issues with certain additives, it is necessary to adjust the polarity of the molecules. However, existing corrosion inhibitors often fail to meet these requirements simultaneously.
[0011] Furthermore, compatibility issues are prominent. Oil and gas field operating fluid systems typically contain various functional additives, such as gelling agents, drag reducers, iron ion stabilizers, and surfactants. Corrosion inhibitors must maintain good compatibility with these additives; otherwise, precipitation, stratification, and instability may occur, affecting the overall operating performance. Due to limitations in their molecular structure, existing corrosion inhibitors often have compatibility issues with certain additives.
[0012] Finally, the cost of use is high. Some high-performance corrosion inhibitors require compounding with multiple additives to achieve the desired effect, leading to complex on-site solution preparation processes and increased costs, further limiting their widespread application. At the same time, the complex synthesis routes and high raw material costs of some corrosion inhibitors also limit their large-scale industrial application.
[0013] Meanwhile, oil and gas field operating fluid systems typically contain a variety of functional additives, such as gelling agents, drag reducers, iron ion stabilizers, and surfactants.
[0014] Existing technology CN201710672378.X discloses an N-methylenenaphthalene chloroquinoline monoquaternary ammonium salt acidizing corrosion inhibitor, prepared by reacting quinoline with 1-chloromethylnaphthalene in isopropanol solvent. When used, it requires the addition of emulsifiers, propynyl alcohol, formamide, and other auxiliaries, and is mainly used for high-temperature acidizing corrosion inhibition in oilfields. This technology involves only simple quaternization of the N atom of the quinoline ring, lacking a 2,4-diaryl substitution structure, resulting in few adsorption sites, loose film formation, and poor high-temperature stability. Multiple auxiliaries must be added to achieve the corrosion inhibition effect; single agents cannot be used directly, leading to complex solution preparation and high costs. The use of organic solvents makes the process environmentally unfriendly and post-processing cumbersome. Furthermore, the lack of electronic effects, hydrophobic effects, and π-π stacking synergistic regulation mechanisms limits the potential for improving corrosion inhibition performance.
[0015] CN201910896870.4 discloses a malonamide-bridged quinoline-based bisquaternary ammonium salt acid pickling corrosion inhibitor, obtained by reacting 6-aminoquinoline with diethyl malonate, followed by quaternization with a brominated alkane, suitable for low-temperature pickling systems of 35-55℃. However, this technology uses a 6-substituted quinoline as the parent core, which is completely different from the 2,4-diarylquinoline parent core structure of this application, lacking a multi-site adsorption design. The malonamide-bridged structure results in poor molecular rigidity and high-temperature instability, limiting its application to low-temperature pickling and failing to meet the high-temperature, strong-acid conditions of oil and gas fields. Furthermore, the lack of aromatic ring substituent regulation mechanisms prevents hydrophobic, dense film formation and π-π stacking-enhanced adsorption capabilities. The complex synthesis steps and reaction conditions make it unsuitable for large-scale industrial production.
[0016] CN202110059136.X discloses a quinolinyl benzimidazole corrosion inhibitor, prepared by acylation, cyclization, chain extension, and quaternization of 1,2,4,5-tetraaminobenzene and quinoline-4-carboxylic acid, for use in room-temperature acid pickling corrosion inhibition of carbon steel and copper. The disclosed technology uses a benzimidazole fused-ring structure as its molecular skeleton, which is completely different from the quinoline core of this application, resulting in a significantly different corrosion inhibition mechanism. The synthetic route is lengthy, requiring multiple reactions and purification steps, leading to high production costs and low efficiency. It lacks a 2,4-diaryl structure and a three-site synergistic control design, resulting in weak high-temperature adsorption and film-forming ability. It is only suitable for room-temperature corrosion scenarios and lacks practicality for high-temperature acid pickling corrosion inhibition.
[0017] CN202410910379.3 discloses an isoquinoline quaternary ammonium salt derivative ultra-high temperature corrosion inhibitor, obtained by multi-component condensation of isoquinoline formaldehyde, cyclohexanedione, and thiourea followed by quaternization. It relies on in-situ polymerization to form a film and requires the addition of an organic antimony synergist. The parent core of this technology is an isoquinoline benzothionone-ketone heterocycle, which is completely different from the structure of 2,4-diarylquinoline; it relies on in-situ polymerization to form a film, resulting in harsh film-forming conditions, poor repeatability, and limited applicability; it must be combined with an organic antimony synergist, which has high toxicity and poor environmental friendliness; and it lacks directional electronic control, hydrophobic densification, and π-π stacking reinforcement design, resulting in an untunable molecular structure and weak performance controllability.
[0018] In addition, some corrosion inhibitors are prone to thermal degradation in high-temperature environments or need to be used in combination with multiple additives, which leads to complicated on-site solution preparation procedures and increased costs, further limiting their promotion and application.
[0019] Therefore, there is an urgent need to develop an oil and gas field corrosion inhibitor that can adapt to high temperature and high pressure environments and has good compatibility and stable corrosion inhibition performance, so as to improve the safety and economy of oil and gas field operations. Summary of the Invention
[0020] To address the above technical problems, the present invention aims to provide a 2,4-diaryl-substituted quinoline corrosion inhibitor containing a 2,4-diarylquinoline core. This core possesses abundant platform modification potential and has promising applications in high-temperature, high-pressure acid corrosion inhibition. During synthesis, it possesses multiple modifiable groups that can be used for (1) electron and adsorption regulation, (2) hydrophobicity and film compactness regulation, and (3) π–π stacking and multi-point adsorption. This allows the quinoline core to have rich directional control methods for compatibility, salt resistance, and temperature resistance of different additives. Furthermore, the quinoline core exhibits good corrosion inhibition effects simply by protonating and quaternizing the nitrogen atoms of quinoline without modification.
[0021] To achieve the above objectives, the present invention adopts the following technical solution: A 2,4-diaryl-substituted quinoline corrosion inhibitor comprising a 2,4-diarylquinoline core having a structure of Formula I:
[0022] (Formula I); Wherein, R1 is a substituted / unsubstituted C6~C18 aryl or heteroaryl group, and the substituent is selected from electron-donating / electron-withdrawing groups, including C1~C8 alkyl, C1~C8 alkoxy, and halogen; R2 is a C1~C18 alkyl substituted / unsubstituted aryl or heteroaryl group; R3 is phenyl, naphthyl, pyridyl, or thiophene; the quinoline N atom may be protonated or quaternized, and the quaternized substituent is a C1~C18 alkyl group.
[0023] As a preferred option, The electron-donating group in R1 includes any one of methyl, methoxyphenyl, and dialkylaminophenyl; The aryl group containing electron-withdrawing substituents in R1 includes any one of chlorophenyl, fluorophenyl, trifluoromethylphenyl, and nitrophenyl. The substituent of R2 is phenyl or C6~C12 alkylphenyl; R3 is phenyl or thiophene group; The quaternized substituent is a C2, C6, or C12 alkyl group.
[0024] Preferably, the corrosion inhibitor is a quaternary ammonium salt product obtained by quaternization of the 2,4-diarylquinoline core with halogenated alkane; The quaternary ammonium salt product is a monotonous quaternary ammonium salt or a ditonous quaternary ammonium salt.
[0025] Preferably, the monomon quaternary ammonium salt is prepared by reacting a 2,4-diarylquinoline core with a haloalkane in a molar ratio of 1:1.0 to 1.5. The gemini quaternary ammonium salt is prepared by reacting a 2,4-diarylquinoline core with a haloalkane at a molar ratio of 1:0.45~0.6. The haloalkanes include brominated C1-C18 alkanes.
[0026] Preferably, the monomorphic quaternary ammonium salt is prepared by reacting a 2,4-diarylquinoline core with a haloalkane in a molar ratio of 1:1.2. The gemini quaternary ammonium salt is prepared by reacting a 2,4-diarylquinoline core with a haloalkane at a molar ratio of 1:0.5. The haloalkane includes any one of bromobutane, bromooctane, and bromododecane.
[0027] A method for preparing a 2,4-diaryl-substituted quinoline corrosion inhibitor includes the following steps: Synthesis of S1,2,4-diarylquinoline nucleus: An equimolar ratio of aniline and benzaldehyde was mixed and reacted under the catalysis of p-toluenesulfonic acid at 100-120°C with stirring and reflux for 6-10 hours. Styrene in an equimolar ratio with aniline was then added dropwise through a constant pressure funnel to carry out a solvent-free reaction, thereby obtaining a 2,4-diarylquinoline core. S2, Quaternization: The 2,4-diarylquinoline core is heated and stirred with haloalkanes at 80~120℃ for 8~15h to obtain mono-quaternary ammonium salts or di-quaternary ammonium salts.
[0028] Preferably, in S1, the molar amount of p-toluenesulfonic acid accounts for 20-40% of the molar amount of aniline; The mixture was stirred and refluxed at 110℃ for 8 hours. The styrene is added over a period of 0.5 to 1.5 hours. The solvent-free reaction takes 3-6 hours; In S2, the 2,4-diarylquinoline core and the haloalkane are heated and stirred at 100°C for 12 hours.
[0029] Preferably, the molar amount of p-toluenesulfonic acid used accounts for 30% of the molar amount of aniline; The styrene was added over a period of 1 hour. The solvent-free reaction lasted for 4 hours.
[0030] The application of a 2,4-diaryl-substituted quinoline corrosion inhibitor in high-temperature acidification of oil and gas fields, wherein the corrosion inhibitor is used in a hydrochloric acid solution with a mass fraction of 10-30 wt% at 60-90°C; The concentration of the corrosion inhibitor is 0.05 wt% to 1 wt%.
[0031] Preferably, the hydrochloric acid solution has a mass fraction of 20 wt%. The concentration of the corrosion inhibitor used is 1 wt%.
[0032] Compared with the prior art, the present invention has at least the following technical effects: This invention provides a 2,4-diaryl-substituted quinoline corrosion inhibitor comprising a 2,4-diarylquinoline core. This core can be modified through 2-position electronic regulation, 4-position hydrophobic regulation, π-π stacking of aromatic rings, and N-atom quaternization to yield monotonous or ditonous quaternary ammonium salts. The core is synthesized solventlessly from aniline, benzaldehyde, and styrene under p-toluenesulfonic acid catalysis. It possesses significant platform modification potential and shows promise for application in high-temperature, high-pressure acid corrosion inhibition.
[0033] During synthesis, it possesses multiple modifiable groups, which can be used for (1) electronic and adsorption regulation; (2) hydrophobicity and membrane compactness regulation; and (3) π–π stacking and multi-point adsorption. This gives the quinoline core a rich range of directional regulation methods for compatibility, salt resistance, and temperature resistance of different additives. Moreover, the quinoline core has good corrosion inhibition effects by protonating and quaternizing the nitrogen atoms of quinoline without modification.
[0034] The preparation method of this 2,4-diaryl-substituted quinoline corrosion inhibitor employs a one-pot process, eliminating the need for intermediate separation and simplifying operation. It involves solvent-free reaction, making it environmentally friendly and reducing wastewater treatment costs. Through multi-active-site synergy, directional structural modification, and mono-quaternization / gemini quaternization modification, it achieves efficient, stable, and compatible corrosion inhibition under high temperature and strong acid conditions.
[0035] This 2,4-diaryl-substituted quinoline corrosion inhibitor exhibits excellent high-temperature resistance: corrosion inhibition efficiency ≥96% at 90℃, with a twin structure ≥98.82%; excellent compatibility: compatible with commonly used oilfield additives, without precipitation, stratification, or deactivation; good water solubility: hydrophilicity is enhanced after quaternization, making it easy to disperse and prepare solutions; simple process: solvent-free, short steps, mild conditions, low waste, suitable for industrialization; controllable cost: no need for large amounts of compounded additives, a single agent can meet high-temperature requirements. Attached Figure Description
[0036] Figure 1 Flowchart of the synthesis method for the 2,4-diarylquinoline core; Figure 2 This is a flowchart of the preparation method for monotonous quaternary ammonium salts; Figure 3 This is a flowchart of the preparation method for geminal quaternary ammonium salts. Detailed Implementation
[0037] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the present invention will be briefly introduced below in conjunction with the accompanying drawings and descriptions of the embodiments or the prior art. Obviously, the following description of the structure of the accompanying drawings is only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. It should be noted that the description of these embodiments is for the purpose of helping to understand the present invention, but does not constitute a limitation of the present invention.
[0038] One specific embodiment of the present invention is as follows: A method for preparing a 2,4-diaryl-substituted quinoline corrosion inhibitor includes the following steps: Synthesis of S1,2,4-diarylquinoline nucleus: Detailed flowchart as follows Figure 1 As shown: An equimolar ratio of aniline and benzaldehyde was mixed, and under the catalysis of p-toluenesulfonic acid, the mixture was stirred and refluxed at 100-120°C. Styrene, in an equimolar ratio with aniline, was then added dropwise through a constant-pressure funnel to carry out a solvent-free reaction, yielding a 2,4-diarylquinoline core. S2, Quaternization: The 2,4-diarylquinoline core is heated and stirred with a haloalkane at 100°C for 12 hours to obtain a mono-quaternary ammonium salt or a di-quaternary ammonium salt.
[0039] The molar amount of p-toluenesulfonic acid used accounts for 30% of the molar amount of aniline and benzaldehyde. The styrene was added over a period of 1 hour. The solvent-free reaction lasted for 4 hours.
[0040] Example 1: A method for preparing a 2,4-diaryl-substituted quinoline corrosion inhibitor includes the following steps: Synthesis of S1,2,4-diarylquinoline nucleus: An equimolar ratio of aniline and benzaldehyde was mixed, stirred and refluxed at 110 °C under the catalysis of p-toluenesulfonic acid, and styrene in an equimolar ratio of aniline was added dropwise through a constant pressure funnel for 5 min, with the dropping rate controlled at 1~2 mL / min. The reaction was carried out in a solvent-free manner for 4 h to obtain the 2,4-diarylquinoline core. S2, Quaternization: The 2,4-diarylquinoline core is heated and stirred with a haloalkane at 100°C for 12 hours to obtain a mono-quaternary ammonium salt or a di-quaternary ammonium salt.
[0041] Aniline: 0.05 mol (4.65 g); Benzaldehyde: 0.05 mol (5.30 g); Styrene: 0.05 mol (5.20 g); p-Toluenesulfonic acid: 0.015 mol (30%, 2.85 g).
[0042] like Figure 2 The diagram shown is a schematic flowchart of the method for preparing monotonous quaternary ammonium salts. like Figure 3 The diagram shown is a schematic flowchart of the preparation method for geminal quaternary ammonium salts.
[0043] Monomeric quaternary ammonium salt M4: Monomeric quaternary ammonium salt M6 can be obtained by mixing 0.05 mol of the synthesized parent nucleus with 0.06 mol of bromobutane and heating and stirring at 100℃ for 8 h (reflux condensation).
[0044] Monomeric quaternary ammonium salt M8: Monomeric quaternary ammonium salt M8 can be obtained by mixing 0.05 mol of the synthesized parent nucleus with 0.06 mol of bromooctane and heating and stirring at 100 °C for 8 h (reflux condensation).
[0045] Monomeric quaternary ammonium salt M12: Monomeric quaternary ammonium salt M12 can be obtained by mixing 0.05 mol of the synthesized parent nucleus with 0.06 mol of bromododecane and heating and stirring at 120 °C for 8 h (reflux condensation).
[0046] Gemini quaternary ammonium salt 2M8: Gemini quaternary ammonium salt 2M8 can be obtained by mixing 0.05 mol of the synthesized core with 0.025 mol of bromooctane and heating and stirring at 100℃ for 12 h (reflux condensation).
[0047] Experimental example: Performance testing: Referring to the standard SY / T 5405-2019 "Test Methods and Evaluation Indicators for Corrosion Inhibitors for Acidizing", the corrosion protection effect of corrosion inhibitors on N80 steel commonly used in oilfield tubing was studied in 60℃, 90℃, and 20 wt% hydrochloric acid solution. Weight loss was measured using N80 steel sheets (50×10×3 mm).
[0048] Before the experiment, the steel sheet was polished until its surface was smooth. After polishing, it was soaked in acetone and cleaned with a soft brush. Then it was soaked in anhydrous ethanol for about 1 minute, dried with cold air, and placed in a dehydrator for 20 minutes. After that, it was weighed (accurate to 0.0001 g) and the weight was recorded.
[0049] Immediately after the test, the steel sheet was cleaned with pure water and its surface was scrubbed with a soft brush. Finally, the sample was rinsed with acetone and anhydrous ethanol, respectively. After drying and reaching constant weight, it was accurately weighed, and the corresponding average corrosion rate (ν) and corrosion inhibition efficiency (ν) of the steel sheet after using different corrosion inhibitors were calculated. ): In the formula, The corrosion rate without corrosion inhibitors is expressed in grams per square meter per hour [g / (m²)] 2 ·h)]; The corrosion rate in the presence of corrosion inhibitors, expressed in grams per square meter per hour [g / (m²)] 2 ·h)]; The time for the weightlessness test is expressed in hours (h). The corrosion loss of the steel sample is expressed in grams (g). The surface area of the steel sheet sample is expressed in square meters (m²). 2 ); The following are the results of the weightlessness test: Table 1. Corrosion inhibition efficiency of alkyl quaternary ammonium salts on N80 carbon steel at different concentrations in 20 wt% hydrochloric acid at 60 and 90 °C.
[0050] Note: m (g): mass of steel sheet corrosion loss; CR (g / (m) 2 • h): Corrosion rate; IEVL (%): Slow-release efficiency CR(g / (m 2 ·h))= m / At· t, where At is the surface area of the steel sheet; t represents the test time.
[0051] IE LW (%) = (1- / ν0)×100% Table 2. Corrosion inhibition efficiency of 2M8 on N80 carbon steel at different concentrations in 20 wt% hydrochloric acid at 90℃.
[0052] The table above shows the following: At 60℃ and 10000mg / L, M12 exhibits a corrosion inhibition efficiency of 96.18%.
[0053] 90℃, 10000mg / L: M8=96.63%; M12=96.83%; 2M8=98.82%.
[0054] Verification example: Theoretical calculations and molecular dynamics simulations verify the mechanism of action of corrosion inhibitors. To further reveal the microscopic mechanism of action of the corrosion inhibitor of this invention, and to verify the structural advantages of the 2,4-diarylquinoline core and the synergistic effect of quaternization modification at the molecular level, density functional theory (DFT) and molecular dynamics (MD) simulation methods were used to systematically study the electronic structure, solution dispersion behavior, interfacial adsorption characteristics and dynamic stability of single-chain quaternary ammonium salts and geminal quaternary ammonium salts.
[0055] 1. Quantum chemical calculations of single-chain quaternary ammonium salts Quantum chemical calculations were performed on the unquaternized disubstituted quinoline core M and three single-chain quaternary ammonium salts M4 (butyl), M8 (octyl), and M12 (dodecyl). Their electrostatic potential distribution, frontier molecular orbitals, and quantization descriptors are shown in Table 3.
[0056] Table 3 Quantum chemical parameters of single-chain quaternary ammonium salts
[0057] The electrostatic potential distribution shows that the lowest electrostatic potential (-43.86 kcal / mol) is near the N atom of the quinoline ring in the parent nucleus M, indicating that this site has a strong electron-donating ability. After quaternization, the N atom changes from neutral to positively charged. The highest electrostatic potential in this region for M4, M8, and M12 is close to 103 kcal / mol, indicating that the lone pair electron-donating ability of the N atom is weakened after quaternization. However, the conjugated aromatic region formed by the quinoline ring and the benzene ring still maintains a low electrostatic potential and is the main active site for molecular-metal surface interaction. The spatial distribution of frontier molecular orbitals (HOMO and LUMO) further shows that the HOMO and LUMO of the four molecules are mainly distributed on the conjugated aromatic ring. The alkyl chain contributes less to the frontier orbitals, and its role is mainly manifested in hydrophobic effects and interfacial barrier construction.
[0058] Quantitative parameters show that, compared to the parent nucleus M, quaternization significantly reduces E_HOMO (weakened electron-donating ability), and E_LUMO decreases simultaneously (enhanced electron-accepting ability), resulting in a smaller band gap ΔE_gap and improved chemical activity. Notably, the quantitative descriptors for M8 and M12 are very close to 0 (the difference in ΔE_gap is only 0.006 eV, and the difference in ΔN is only 0.002), indicating that once the alkyl chain reaches C8 length, further increases in chain length have very limited effect on improving the molecular electronic structure and intrinsic adsorption activity.
[0059] M12 does not have a significant advantage over M8 at the electronic level, which provides a theoretical basis for the subsequent optimization of C8 chain length to construct geminal quaternary ammonium salts.
[0060] 2. Molecular dynamics simulation of single-chain quaternary ammonium salts (1) Solution dispersion behavior Molecular dynamics simulations were used to investigate the dispersion and aggregation behavior of M4, M8, and M12 at different concentrations (500, 1000, 2500, 5000, and 10000 ppm) in 20 wt% hydrochloric acid solution. Simulation results showed that M4 exhibited good dispersibility at all concentrations; M8 dispersed well at low concentrations, but began to aggregate locally at 2500 ppm, although it maintained basic aqueous dispersion at 10000 ppm; while M12 formed significant aggregates at 5000 ppm and 10000 ppm, exhibiting poor acid compatibility.
[0061] Quantitative analysis of solvent accessible surface area (SASA) further confirmed the above trend (Table 4). At a low concentration of 500 ppm, the SASA of M4, M8, and M12 were 3.120, 3.676, and 4.219 nm, respectively. 2 The results are consistent with the molecular size distribution, indicating that all three molecules can be dispersed well. As the concentration increases to 10,000 ppm, the SASA of M4 decreases by 29.8%, M8 by 44.0%, and M12 by a significant 56.2%. Particularly noteworthy are the lower SASA of M12 at 5,000 ppm and 10,000 ppm, indicating that it undergoes significant self-aggregation at high concentrations due to strong hydrophobicity. These results suggest that while M8 exhibits a certain tendency for interfacial enrichment, it can maintain good aqueous dispersion, while the excessive hydrophobicity of M12 is detrimental to uniform dispersion in acidic solutions.
[0062] Table 4. Average solvent-accessible surface area (nm) of M4, M8, and M12 at different concentrations. 2 )
[0063] (2) Adsorption behavior at the iron layer interface Adsorption simulations in the 20 wt% hydrochloric acid / Fe(110) interface system showed that only a small portion of M4 molecules adsorbed on the surface at low concentrations, indicating limited interfacial adsorption. M8 migrated to the iron surface and adsorbed in a planar manner at low concentrations, with the number of adsorbed molecules increasing with increasing concentration, forming a continuous and uniform adsorption protective layer at high concentrations. M12 exhibited the strongest aggregation tendency, with molecular clusters observed even at low concentrations, and forming a significant thick layer at high concentrations—this thick layer was more of a localized accumulation of disordered clusters on the surface than a continuous film formed by uniform planar deposition.
[0064] The statistical analysis of the contact numbers between corrosion inhibitor molecules and the iron surface (Table 5) shows that M8 reached 780 contacts at 500 ppm, significantly higher than M4 and M12; at 10000 ppm, the number increased to approximately 4750, and the contact number curve showed the least fluctuation, indicating that its interfacial adsorption state was the most stable. Regarding the minimum contact distance, the three corrosion inhibitors tended to be close at high concentrations (approximately 0.219 nm), indicating that the difference in interfacial adsorption capacity mainly lies in the number and coverage area of molecules that stably occupy the surface, rather than their ability to approach the surface. In summary, M8 exhibits the optimal interfacial adsorption characteristics—effectively occupying the surface to form a high-coverage adsorption layer while avoiding the non-uniform accumulation caused by excessive aggregation in M12.
[0065] Table 5. Number of contacts between corrosion inhibitor and iron layer at different concentrations (representative concentrations selected)
[0066] 3. Quantum chemical calculations and mechanistic analysis of the geminal quaternary ammonium salt 2M8 The quantum chemical parameters of the selected C8-chain single-chain quaternary ammonium salt M8 and its bipolar structure 2M8 were compared (Table 6). The ESP distribution of 2M8 shows that the region near the N atom in the two quaternary ammonium salt head groups has the highest overall electrostatic potential (maximum value 138.05 kcal / mol), higher than M8's 103.19 kcal / mol, indicating that the two positively charged centers in the bipolar structure further enhance the overall positive charge of the molecule. The conjugated aromatic ring system composed of the quinoline rings and benzene rings on both sides maintains a low electrostatic potential, providing active sites for π electrons to participate in interfacial interactions. The HOMO and LUMO of 2M8 are mainly distributed on the conjugated aromatic ring system on both sides, with obvious distribution in both quinoline head group regions, indicating that 2M8 possesses a structural basis for dual-site adsorption.
[0067] Table 6 Comparison of quantum chemical parameters of M8 and 2M8
[0068] Quantitative parameters show that 2M8 exhibits a lower E_HOMO (due to the two quaternary ammonium salt positively charged centers reducing the overall electron cloud density), a simultaneously decreased E_LUMO (due to enhanced electron-accepting ability), an electrophilic index ω increasing from 5.731 eV to 6.581 eV, and an electron transfer fraction ΔN decreasing to -0.104. This indicates that the interfacial interaction mode of the diconic molecules does not shift towards stronger electron-donating adsorption, but rather further enhances their tendency to accept electrons fed back from the metal surface. Simultaneously, the two symmetrically distributed adsorption regions provide the structural conditions for dual-site anchoring. These results theoretically support the corrosion inhibition mechanism of the "diconic anchoring effect" proposed in this invention.
[0069] 4. Dynamic stability simulation of the adsorption layer of Gemini quaternary ammonium salt 2M8 To simulate the scouring effect of fluid flow on the adsorbed layer during acidizing operations in oil and gas fields, the stability of the adsorbed layers of M8, M12, and 2M8 was compared under low shear (10 kJ / mol / nm) and high shear (200 kJ / mol / nm) conditions.
[0070] Under low shear conditions, both M8 and 2M8 maintained continuous surface coverage and stable adsorption layer morphology. The cluster structure of M12 was disrupted by disturbance, and molecules detached from the interface and re-aggregated after entering the solution, leading to a decrease in interfacial protection. Under high shear conditions, M8 exhibited significant desorption, with a gradual decrease in surface coverage. M12 desorption was more severe, with rapid destruction of the cluster structure and near loss of surface coverage. 2M8, however, demonstrated the best adsorption layer retention capacity; although some molecules desorbed, it maintained a high degree of adsorption coverage, and the desorbed molecules remained dispersed in the solution, preserving the possibility of re-adsorption onto the iron surface.
[0071] Density distribution analysis along the z-direction further confirms (Table 7) that the bulk density of 2M8 solution is close to zero under no-shear and low-shear conditions, with the interfacial density peak at approximately 1200 kg / m³. -3 (Highest of the three); Under a shear force of 50 kJ / mol / nm, the bulk density only increases to about 50 kg / m³. -3 The adsorption capacity of 2M8 was significantly lower than that of M8 and M12 under the same conditions; under strong shear conditions, 2M8 still retained the most adsorbed molecules at the interface. These results indicate that the dual-headed anchoring structure of 2M8 endows the adsorption layer with excellent resistance to flow erosion, a characteristic that is particularly important for dynamic conditions in high-temperature acidizing operations in oil and gas fields.
[0072] Table 7 Comparison of interfacial adsorption retention rates of corrosion inhibitors under different shear conditions
[0073] Mechanism Summary Based on the above theoretical calculations and molecular dynamics simulations, the mechanism of action of the 2,4-diaryl-substituted quinoline corrosion inhibitor of this invention can be summarized as the following synergistic effects: (1) The conjugated aromatic ring system of the quinoline core provides a π-electron enrichment region, serving as the main active site for interaction with the metal surface; (2) After quaternization, the positively charged N atom provides electrostatic adsorption, while the electron-accepting tendency of the molecule is enhanced, allowing it to accept feedback electrons from the metal surface; (3) The C8 alkyl chain achieves an optimal balance between hydrophobic effect and solution dispersibility, providing sufficient hydrophobic barrier while avoiding excessive aggregation; (4) The twin structure provides dual-site anchoring capability, significantly enhancing the dynamic stability of the adsorption layer. The above multi-effect synergistic mechanism together constitutes the molecular basis for the excellent corrosion inhibition performance of the corrosion inhibitor of this invention under high temperature and strong acid conditions.
[0074] Finally, it should be noted that the above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A 2,4-diaryl-substituted quinoline corrosion inhibitor, characterized in that, The corrosion inhibitor comprises a 2,4-diarylquinoline core, having the structure of Formula I: (Formula I); In this configuration, R1 is a substituted / unsubstituted C6-C18 aryl or heteroaryl group, with the substituent selected from electron-donating / electron-withdrawing groups, including C1-C8 alkyl, C1-C8 alkoxy, and halogens; R2 is a C1-C18 alkyl substituted / unsubstituted aryl or heteroaryl group; R3 is phenyl, naphthyl, pyridyl, or thiophene; the quinoline N atom may be protonated or quaternized, with the quaternized substituent being a C1-C18 alkyl group. 。 2. The 2,4-diaryl-substituted quinoline corrosion inhibitor according to claim 1, characterized in that, The electron-donating group in R1 includes any one of methyl, methoxyphenyl, and dialkylaminophenyl; The aryl group containing electron-withdrawing substituents in R1 includes any one of chlorophenyl, fluorophenyl, trifluoromethylphenyl, and nitrophenyl. The substituent of R2 is phenyl or C6~C12 alkylphenyl; R3 is phenyl or thiophene group; The quaternized substituent is a C2, C6, or C12 alkyl group.
3. The 2,4-diaryl-substituted quinoline corrosion inhibitor according to claim 1, characterized in that, The corrosion inhibitor is a quaternary ammonium salt product obtained by quaternization of the 2,4-diarylquinoline core with halogenated alkane. The quaternary ammonium salt product is a monotonous quaternary ammonium salt or a ditonous quaternary ammonium salt.
4. The 2,4-diaryl-substituted quinoline corrosion inhibitor according to claim 3, characterized in that, The monomorphic quaternary ammonium salt is prepared by reacting a 2,4-diarylquinoline core with a haloalkane in a molar ratio of 1:1.0 to 1.
5. The gemini quaternary ammonium salt is prepared by reacting a 2,4-diarylquinoline core with a haloalkane at a molar ratio of 1:0.45~0.
6. The haloalkanes include brominated C1-C18 alkanes.
5. A 2,4-diaryl-substituted quinoline corrosion inhibitor according to claim 4, characterized in that, The monomorphic quaternary ammonium salt is prepared by reacting a 2,4-diarylquinoline core with a haloalkane in a molar ratio of 1:1.
2. The gemini quaternary ammonium salt is prepared by reacting a 2,4-diarylquinoline core with a haloalkane at a molar ratio of 1:0.
5. The haloalkane includes any one of bromobutane, bromooctane, and bromododecane.
6. A method for preparing the 2,4-diaryl-substituted quinoline corrosion inhibitor as described in any one of claims 1 to 5, characterized in that, Includes the following steps: Synthesis of S1,2,4-diarylquinoline nucleus: An equimolar ratio of aniline and benzaldehyde was mixed and reacted under the catalysis of p-toluenesulfonic acid at 100-120°C with stirring and reflux for 6-10 hours. Styrene in an equimolar ratio with aniline was then added dropwise through a constant pressure funnel to carry out a solvent-free reaction, thereby obtaining a 2,4-diarylquinoline core. S2, Quaternization: The 2,4-diarylquinoline core is heated and stirred with haloalkanes at 80~120℃ for 8~15h to obtain mono-quaternary ammonium salts or di-quaternary ammonium salts.
7. The method for preparing the 2,4-diaryl-substituted quinoline corrosion inhibitor according to claim 6, characterized in that, In S1, the molar amount of p-toluenesulfonic acid accounts for 20-40% of the molar amount of aniline; The mixture was stirred and refluxed at 110℃ for 8 hours. The styrene is added over a period of 0.5 to 1.5 hours. The solvent-free reaction takes 3-6 hours; In S2, the 2,4-diarylquinoline core and the haloalkane are heated and stirred at 100°C for 12 hours.
8. The method for preparing the 2,4-diaryl-substituted quinoline corrosion inhibitor according to claim 7, characterized in that, The molar amount of p-toluenesulfonic acid used is 30% of the molar amount of aniline; The styrene was added over a period of 1 hour. The solvent-free reaction lasted for 4 hours.
9. The application of a 2,4-diaryl-substituted quinoline corrosion inhibitor as described in any one of claims 1 to 5 in high-temperature acidizing of oil and gas fields, characterized in that, The corrosion inhibitor is used at 60-90°C in a hydrochloric acid solution with a mass fraction of 10-30 wt%. The concentration of the corrosion inhibitor is 0.05 wt% to 1 wt%.
10. The application according to claim 9, characterized in that, The hydrochloric acid solution has a mass fraction of 20 wt%. The concentration of the corrosion inhibitor used is 1 wt%.
Citation Information
Patent Citations
Acidification corrosion inhibitor as well as preparation method and application thereof
CN107384362A
A quinoline-based bisquaternary ammonium salt type pickling corrosion inhibitor and its preparation method
CN110642784B
Quinolyl benzimidazole corrosion inhibitor and preparation method thereof
CN112851694A
An ultra-high temperature corrosion inhibitor
CN118852107B